Identification of stress-responsive transcription factors with protein-bound Escherichia coli genomic DNA libraries - Xianqiang Li; Xin Jiang; Meiying Xu; Yun Fang; Yan Wang; Guoping Sun; Jun Guo (AMB Express, 2020)
Abstract Bacteria promoters along with operators are crucial elements in the control of gene expression in microbes in response to environmental stress changes. A genome-wide promoter DNA regulatory library is in demand to be developed for a microbe reporter method to monitor the existence of any given environmental stress substance. In this study, we utilized Escherichia coli (E. coli) as a model system for the preparation of both cell lysates and genomic DNA fragments. Through enriching protein-bound DNA fragments to construct luciferase reporter libraries, we found that, of 280 clones collected and sequenced, 131 clones contained either the promoter-35 and -10 conservative sequences and/or an operator transcription factor binding sites (TFBS) region. To demonstrate the functionality of the identified clones, five of 131 clones containing LexA binding sequence have been demonstrated to be induced in response to mitomycin C treatment. To evaluate our libraries as a functional screening library, 80 randomly picked up clones were cultured and treated with and without MMC, where two clones were shown to have greater than twofold induction. In addition, two arsenite-responsive clones were identified from 90 clones, one having the well-known ArsR and another having the osmotically inducible lipoprotein (OsmE1). The newly discovered osmE1 has been quantitatively validated to be induced by arsenite treatment with real-time PCR in a dose response and time course manner. This enriching protein-bound DNA luciferase reporter libraries and functional screening facilitate the identification of stress-responsive transcriptional factors in microbes. We developed functional libraries containing E. coli genomic-wide protein-bound DNA as enhancers/operators to regulate downstream luciferase in response to stress.